Challenges and opportunities of molecular epidemiology: using omics to address complex One Health issues in tropical settings - Tigistu-Sahle, Feven; Mekuria, Zelalem H.; Satoskar, Abhay R.; Sales, Gustavo F. C.; Gebreyes, Wondwossen A.; Oliveira, Celso J. B. (Frontiers in Tropical Diseases, 2023)
The molecular biology tools available since the early 1970s have been crucial to the development of molecular epidemiology as an important branch of public health, and are used for the identification of host genetic and environmental factors associated with both communicable (CDs) and non-communicable diseases (NCDs) across human and animal populations. Molecular epidemiology has significantly contributed to the understanding of etiological agents, disease distribution, and how to track outbreaks, as well as to prevention and control measures against tropical infectious diseases. However, there have been significant limitations compromising the successful application of molecular epidemiology in low-to-middle income countries (LMICs) to address complex issues at the animal–human–environment interface. Recent advances in our capacity to generate information by means of high-throughput DNA genomic sequencing, transcriptomics, and metabolomics have allowed these tools to become accessible at ever-lower costs. Furthermore, recently emerged omics fields such as lipidomics are improving our insights into molecular epidemiology by measuring lipid phenotypes that gauge environmental and genetic factors in large epidemiological studies. In parallel, the development of bioinformatic tools has revolutionized the utility of omics, providing novel perspectives to better characterize pools of biological molecules and translate them into the structure, function, and dynamics of organisms. Unfortunately, the use of such powerful tools has not been optimal for a One Health approach to both CDs and NCDs, particularly in low-resource tropical settings. The aim of this review is to present the fundamentals of omics tools and their potential use in molecular epidemiology, and to critically discuss the impact of omics on the evolving One Health dimension applied to tropical diseases. We use Ethiopia and Brazil as model systems to illustrate existing gaps and opportunities, while also addressing global applications. Moreover, we also discuss perspectives on exploring omics based molecular epidemiology in the context of One Health as a crucial approach to preventing and mitigating the burden of CDs and NCDs at the interface of human health, animal health, and the environment. This review shows that building capacity in the tropical regions is crucial to establishing equitable global health.